Decreased Expression of CD14 in MSU-Mediated Inflammation May Be Associated with Spontaneous Remission of Acute Gout - Lihua Duan; Jiao Luo; Qiang Fu; Ke Shang; Yingying Wei; Youlian Wang; Yan Li; Jie Chen (Journal of Immunology Research)
Gout is a common metabolic disease in humans, and it is due to persistently elevated levels of uric acid in the blood. At high levels, uric acid crystallizes and the crystals deposit in joints and surrounding tissues, resulting in an attack of gout. Interestingly, the gout attack can spontaneously resolve within a few days. However, the self-limited mechanism of gout remains elusive. It has been demonstrated that CD14 plays an important role in self-remission of gout. In this study, we found that the proportion of CD14-positive PBMCs was decreased in gout patients when compared with healthy controls and the serum sCD14 level was also considerably decreased in gout patients in comparison to healthy controls. In addition, sCD14 levels were positively correlated with CRP levels. Furthermore, the effect of MSU on the levels of CD14 in healthy volunteer’s PBMC was explored in in vitro experiment. The results showed that CD14 expression on macrophage and sCD14 levels in the culture supernatants were significantly decreased after MSU treatment. However, there was no significance in the levels of membrane CD14 and sCD14 in healthy volunteer’s PBMC stimulated by LPS. Taken together, these results suggest that CD14 might play an important role in self-remission of gout.